Electrochemical detection of DNA hybridization by a zirconia modified diamond electrode - Liu, B; Hu, J; Foord, J (2012)
The use of a zirconia thin layer coating to attach phosphate terminated DNA oligonucleotides to a diamond electrode was explored. This DNA functionalised electrode shows an enhanced redox response to the redox mediator methylene blue, which is quenched in the presence of complementary DNA oligonucleotides, enabling the highly sensitive and selective detection of such species in solution. The study shows that the electrodeposition of zirconia on diamond electrodes can be used as an effective and easily implemented route for surface functionalisation and biosensor fabrication using this electrode material. © 2012 Elsevier B.V. All rights reserved.